2018
DOI: 10.1523/jneurosci.0066-18.2018
|View full text |Cite
|
Sign up to set email alerts
|

Neural Coding of Whisker-Mediated Touch in Primary Somatosensory Cortex Is Altered Following Early Blindness

Abstract: Sensory systems do not develop and function independently of one another, yet they are typically studied in isolation. Effects of multisensory interactions on the developing neocortex can be revealed by altering the ratios of incoming sensory inputs associated with different modalities. We investigated neural responses in primary somatosensory cortex (S1) of short-tailed opossums (; either sex) after the elimination of visual input through bilateral enucleation very early in development. To assess the influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 80 publications
1
29
0
Order By: Relevance
“…The goal of this study was to examine and quantify the effects of early bilateral enucleation on corticocortical and thalamocortical connections of the primary somatosensory cortex (S1) in short-tailed opossums and to compare these to connections of S1 in sighted opossums (Dooley et al, 2013(Dooley et al, , 2015. The present investigation was prompted by the finding that following very early enucleation, the primary somatosensory cortex increases in size (Karlen et al, 2006), neurons in S1 respond to both somatosensory and auditory stimulation (Kahn & Krubitzer, 2002;Karlen et al, 2006) and the neural response properties and receptive field size are altered compared to sighted controls (Ramamurthy & Krubitzer, 2018; Figure 1). Here, we provide anatomical evidence for both novel corticocortical projections, as well FIGURE 8 Location of retrogradely labeled neurons in the thalamus resulting from an injection of CTB in S1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The goal of this study was to examine and quantify the effects of early bilateral enucleation on corticocortical and thalamocortical connections of the primary somatosensory cortex (S1) in short-tailed opossums and to compare these to connections of S1 in sighted opossums (Dooley et al, 2013(Dooley et al, , 2015. The present investigation was prompted by the finding that following very early enucleation, the primary somatosensory cortex increases in size (Karlen et al, 2006), neurons in S1 respond to both somatosensory and auditory stimulation (Kahn & Krubitzer, 2002;Karlen et al, 2006) and the neural response properties and receptive field size are altered compared to sighted controls (Ramamurthy & Krubitzer, 2018; Figure 1). Here, we provide anatomical evidence for both novel corticocortical projections, as well FIGURE 8 Location of retrogradely labeled neurons in the thalamus resulting from an injection of CTB in S1.…”
Section: Discussionmentioning
confidence: 99%
“…In most of the animals examined using neurophysiological mapping techniques, both auditory and somatosensory cortex were reorganized as well. Bottom figures are adapted from Kahn and Krubitzer (2002) and Karlen et al (2006) (Ramamurthy & Krubitzer, 2018). Although it is likely that these functional alterations in S1 are the result of altered connectivity at multiple levels of the nervous system, there are no studies that examine the connections of the primary somatosensory cortex following early loss of vision.…”
Section: (B)mentioning
confidence: 99%
See 1 more Smart Citation
“…Work from our laboratory has recently shown that neurons in the whisker representation of S1 have smaller receptive fields and increased selectivity (i.e. greater discriminability) (Ramamurthy & Krubitzer, 2018). Thus, we sought to examine the role of the whiskers during variable ladder rung walking.…”
Section: Performance Deficits and Limb Trajectories Are Altered To Grmentioning
confidence: 99%
“…Similar to rodents, neurons in the reorganized visual cortex of early blind opossums respond instead to deflections of the whiskers and broadband auditory clicks (Karlen et al, 2006). The spared sensory systems are also affected, as early blind opossums exhibit changes in the cortical connections of S1, as well as changes in receptive field size and response properties of neurons in the whisker representation of S1 (Dooley & Krubitzer, 2019;Ramamurthy & Krubitzer, 2018).…”
Section: Introductionmentioning
confidence: 99%